Freedom and Personal Autonomy as the Foundation of Private International Law and the Cornerstone of Individual Rights in the AI Era - Antoni Abat i Ninet (Journal of Liberty and International Affairs)
An examination of private international law manuals and relevant legislation demonstrates that the autonomy of the will constitutes a fundamental epistemological principle underpinning the field. However, this freedom is neither absolute nor unbounded. The binding force of pacta sunt servanda, the limitations imposed by public law, the operation of mandatory rules (lois de police), the demands of public policy (ordre public), and the necessity of protecting weaker parties all constrain its exercise. In contemporary private international law, the principle has evolved into a pervasive and dynamic norm, deeply embedded in legal practice while continuously adapting to new challenges. In the emerging era of artificial intelligence, the autonomy of the will must be reaffirmed as a cornerstone of individual rights, ensuring the preservation of personal freedom amidst technological transformations.